The influence of metaverse environment design on the quality of experience in virtual reality classes: a comparative study - Uribe, Valentina; Figueroa, Pablo; Gomez, Vivian (Frontiers in Education, 2024)
We are interested in how metaverse technologies can provide an environment for future virtual education beyond traditional videoconferencing technologies. This study investigates learning and the quality of the classroom experience by conducting classes in four metaverse environments: Meta Horizon Workrooms, Spatial, Mozilla Hubs, and Arthur. Through the analysis of questionnaires, we assess the influence of factors such as avatars, spatial arrangement, mobility, and extra functionalities on concentration, usability, presence, and learning. While we did not observe significant differences in learning outcomes, our analysis reveals substantial variations in the quality of the classroom experience. Specifically, higher immersion, concentration, and presence levels were observed in metaverses with limited movement and functionalities. Also, our findings emphasize the positive impact of avatars with realistic facial expressions on enhancing the overall experience. Finally, we present lessons learned and offer recommendations for class configurations in the metaverse based on our questionnaire analysis.